2019
DOI: 10.1016/j.fm.2019.103268
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of Shiga toxin-producing Escherichia coli from Norwegian bivalves

Abstract: P a g e | 1 P a g e | 2 ABSTRACT Only few studies concerning Shiga toxin-producing E. coli (STEC) detection in coastal environments and bivalves have been reported and there have been no reported outbreaks by STEC from bivalves in the world.The aim of this thesis was to investigate the occurrence of STEC in Norwegian bivalves, and to characterize potential STEC isolates obtained from the samples.To improve our understanding of STEC, the occurrence was investigated in 269 bivalves collected from harvesting area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…4 ). The final stx 2 variant was recovered from an E. coli isolate isolated from periphyton with a toxin type most similar to that of stx 2i , whose toxin product has yet to be characterized but has not been associated with clinical disease and has been recovered only from raw milk ( 19 ) and bivalves ( 37 ). Other STEC-associated virulence factors ( esp P, etp D, ehx A, iha , and ter ZABCDE) were uncommon and were often identified in isolates that were stx or eae positive (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…4 ). The final stx 2 variant was recovered from an E. coli isolate isolated from periphyton with a toxin type most similar to that of stx 2i , whose toxin product has yet to be characterized but has not been associated with clinical disease and has been recovered only from raw milk ( 19 ) and bivalves ( 37 ). Other STEC-associated virulence factors ( esp P, etp D, ehx A, iha , and ter ZABCDE) were uncommon and were often identified in isolates that were stx or eae positive (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in another study, all the examined shellfish samples from landing centers and retail fish markets were positive for E. coli (100%) (Prakasan et al 2018). In this regard, Martin and his co-authors reported that any edible marine shellfish species found exposed to fecal contamination, could be regarded as a potential source of STEC (Martin et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Although ruminants are the main reservoirs for STEC, other sources including wildlife, marine environment, and aquaculture could be possible spillover hosts for these bacteria (Kamala et al 2022;Kim et al 2020). Although previous studies have documented presence of several pathogens, there have been few reports on STEC spreading densities from coastal and marine environment (Baliere et al 2015;Kamala et al 2022;Martin et al 2019;Prakasan et al 2018). The present study aims to investigate to which level STEC and their virulence factors are present on the surfaces and accumulated in the tissues of shellfish at harvesting areas of Lake Timsah, Ismailia, Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Stx2 presents several different variants (Stx2a to Stx2g), which have high homology (93–100%), except for Stx2f variant (69% identity) [12]. Furthermore, two additional Stx2 types, Stx2h and Stx2i, were recently described [13,14]. STEC strains encoding Stx2 are more frequently related to the most severe cases of HUS [15] and the subtype Stx2a cause more serious illnesses than strains encoding Stx2c [16].…”
Section: Introductionmentioning
confidence: 99%